Leveraging Digital Solutions to Fight COVID-19 : Lessons from ASEAN Countries - Clavier, Fabien; Ghesquiere, Francis (World Bank, Washington, DC, 2021)
Digital solutions have been the signature of Southeast Asia’s response to COVID-19 (coronavirus). Technologies used during the crisis have helped address a wide spectrum of problems, supporting public health efforts, public communication, and economic and social policies. This policy brief explores how ASEAN countries have leveraged digital technologies to fight COVID-19 and investigates the roles of governments, local technology ecosystems, and citizens in deploying such solutions. The findings suggest that the development and use of digital solutions have accelerated collaboration between different spheres of governments, technology companies, research entities, and society at large. The COVID-19 crisis has also highlighted the digital divide across the region and the challenges in ensuring technological changes in the ASEAN region as a whole.